Circulating tumor DNA: Response Evaluation Criteria in Solid Tumors – can we RECIST? Focus on colorectal cancer - Karen-Lise Garm Spindler; Anders Jakobsen (Therapeutic Advances in Medical Oncology, 2023)
Interest in the measurement of circulating tumor DNA (ctDNA) in colorectal cancer (CRC) has increased during the past decade. The analysis of quantitative ctDNA changes as a general response evaluation criterion during systemic treatment is a scientific approach with high clinical potential, and results can be transferred to a pan-cancer concept if relevantly investigated. The purpose of this overview is to discuss the current evidence for ctDNA as a marker of response in metastatic CRC (mCRC) and to propose criteria for definitions of response to systemic therapies applicable in prospective clinical trials. We discuss the literature, which supports a new definition of ctDNA Response Evaluation Criteria in Solid Tumors. Finally, we discuss the challenges in preparations of the optimal trial design to establish the true clinical utility of ctDNA.